Morphometric measurement and management of Beetal goats in Ambala district of Haryana - Maroof Ahmad; Singh, PK (Journal of Livestock Biodiversity, 2025)
Data on 153 adult Beetal goats belonging to 6 villages of 4 blocks of Ambala district were utilized for the present study. The mean ± S.E. of body length, height at withers, chest girth, paunch girth, ear length, ear width, tail length, udder circumference, length of teat and body weight were estimated to be  71.43 ± 0.36, 74.29 ± 0.38, 78.35 ± 0.53, 87.14 ± 0.64, 22.18 ± 0.38, 10.32 ± 0.14, 19.22 ± 0.21, 28.84 ± 0.22, 11.63 ± 0.34 cm and 44.06 ± 0.44 kg respectively in adult females. Average of body weight at sexual maturity, age at  first conception, age at  first kidding, kidding interval and gestation length were observed as 26.85 ± 2.11 kg, 372.29 ± 4.48, 516.33 ± 3.19, 348.72 ± 4.41 and 147.52 ± 2.64 days, respectively. Beetal goats were raised under grazing system of management and some prophylactic treatments of the goats were practiced by the farmers in Ambala district.